1987
DOI: 10.1042/cs0730197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mannitol, lactulose and 51Cr-labelled ethylenediaminetetra-acetate as markers of intestinal permeability in man

Abstract: 1. Factors affecting the intestinal uptake and urinary excretion of mannitol, lactulose and 51Cr-labelled ethylenediaminetetra-acetate (51Cr-EDTA), have been investigated in normal subjects and three patients with ileostomy. 2. The distribution volume of markers within the body, the rate of disappearance from plasma and renal clearance were assessed after an intravenous injection of a mixture of mannitol (2 g), [14C]mannitol (10 microCi), lactulose (0.1 g) and 51Cr-EDTA (5 microCi). 3. The urinary recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 0 publications
3
42
1
Order By: Relevance
“…However, where the mucosa is damaged, larger amounts of lactulose cross the intestinal barrier into the blood, so lactulose uptake can be regarded as an index of leakiness (Ford et al 1985). Within the body both probes remain intact, they remain in the extracellular fluid compartment and both are rapidly excreted by the kidneys (Elia et al 1987). Consequently, the amounts found in the urine reflect the amounts taken up by the two different routes in the small intestine.…”
Section: Malnutrition: Gastrointestinal Enteropathy: Intestinementioning
confidence: 99%
“…However, where the mucosa is damaged, larger amounts of lactulose cross the intestinal barrier into the blood, so lactulose uptake can be regarded as an index of leakiness (Ford et al 1985). Within the body both probes remain intact, they remain in the extracellular fluid compartment and both are rapidly excreted by the kidneys (Elia et al 1987). Consequently, the amounts found in the urine reflect the amounts taken up by the two different routes in the small intestine.…”
Section: Malnutrition: Gastrointestinal Enteropathy: Intestinementioning
confidence: 99%
“…ingestion of lactulose and rhamnose showed that during kwashiorkor, abnormal intestinal permeability correlated with disease severity and improved only slowly with nutritional rehabilitation (Brewster et al 1997). Elia et al (1987) investigated the factors affecting the intestinal uptake and urinary excretion of mannitol (M), lactulose (L) and Cr-EDTA in normal subjects and three patients with ileostomy. They suggested that the uptake of L is slower than that of M, and Cr-EDTA is readily absorbed in the colon.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…This value is close to that found using the 51 Cr-EDTA radiomarker in rats (2.8%; Ramage et al, 1988) but higher than the excretion recorded in humans (0.44-0.85%; Maxton et al, 1986;André et al, 1990). The 24-h recovery of Cr-EDTA in urine seems to represent marker absorption in both small and large intestines (Maxton et al, 1986;Elia et al, 1987). It is between 1.2 and 2.6% in healthy humans (Maxton et al, 1986;André et al, 1990) and close to 12% in dogs (Hall etal, 1989; (Haeney etal, 1978;Lim etal, 1993), 12-16% in preruminant calves (Seegraber and Morrill, 1986;Dawson et al, 1988) and 10% in mares (Bolton et al, 1976).…”
mentioning
confidence: 99%